PENGRAJIN KAYU DARI CIAMIS KOTA MAMPU MENGGEBRAK PEREKONOMIAN - Rahmah, Fadila; Apriliani, Silvi; Ramdhani, Tasya Nur; Sianturi, Risbon (Institut Shanti Bhuana, Program Studi Kewirausahaan, 2024)
A wood craftsman is an individual or group of people who work in the field of handicrafts. By using wood as basic materials, craftsmen are able to produce various products. So this research aims to analyze the strategies of wood craftsmen in marketing and the obstacles to increasing the number of sales in Ciamis City. This research is a descriptive qualitative type, where data collection is carried out by means of observation and interviews. And then analyzed using the SWOT Method which is a strategic planning tool used to evaluate the strengths, weaknesses, opportunities and threats of a business or individual. The results of the research show that Mr Jenal, a wood craftsman from Ciamis, has the potential to disrupt the family's economy in several ways, such as: Creating high quality products that are in demand by many consumers. Focusing on selecting raw materials has an influence on increasing demand and sales which generate profits. The direct sales process in strategic locations really influences the market effectively, this influences increasing profitability and strengthening the local economy